Efektivitas Susu Tinggi Protein dalam Menurunkan Berat Badan dan Pencegahan Obesitas: Scoping Review - Cice Tresnasari; Dony Septriana Rosady; Akbar Paulana (Bandung Conference Series: Medical Science, 2023)
Abstract. Obesity is a condition of excess fat accumulation in the body which results in complex multifactorial disease. Obesity can be corrected by providing a low-calorie diet, one of which is milk. This study aims to determine the effectiveness of giving milk as high-protein diet in weight loss therapy in obese patients. The research method used was scoping review, with analytic observational study articles (cohort, case-control and cross-sectional) obtained from ScienceDirect, Springerlink, PubMed Central, BioMed Central and Nature databases. Then the identified journals were screened with inclusion criteria with the number of journals after screening as many as 3,429 articles. After that, it was adjusted for exclusions so the remaining number was 4 articles. Then critical appraisal was carried and final article that met the requirements was obtained with total 4 articles. From the results of the analysis, it was found that there was a significant decrease in body weight in obese adults after being given intervention in form of high-protein milk in the first two years. The conclusion of this study shows that milk with low fat content is effective in causing weight loss in obese adults. Abstrak. Obesitas adalah keadaan penumpukan lemak berlebih di dalam tubuh yang mengakibatkan complex multifactorial disease. Keadaan obesitas dapat diperbaiki dengan cara memberi diet rendah kalori, salah satunya adalah pemberian susu. Penelitian ini bertujuan mengetahui efektivitas pemberian susu sebagai diet tinggi protein dalam terapi penurunan berat badan pada penderita obesitas. Metode penelitian yang digunakan adalah scoping review, dengan artikel berstudikan observasional analitik (kohort, kasus kontrol dan potong lintang) yang didapatkan dari database ScienceDirect, Springerlink, PubMed, PubMed Central, BioMed Central dan Nature. Kemudian jurnal yang teridentifikasi dilakukan skrining kriteria inklusi dengan jumlah jurnal setelah dilakukan skrining sebanyak 3.429 artikel. Setelah itu disesuaikan dengan kriteria ekslusi sehingga jumlah tersisa 4 artikel. Selanjutnya dilakukan critical appraisal dan didapatkan artikel akhir yang eligible dengan jumlah 4 artikel. Hasil analisis didapatkan penurunan berat badan secara signifikan pada obesitas dewasa setelah diberikan intervensi berupa susu rendah lemak dalam dua tahun pertama. Susu dengan kadar tinggi protein dapat menimbulkan penurunan berat badan pada obesitas pada orang dewasa. Kesimpulan penelitian ini menunjukkan susu dengan kadar protein tinggi efektif dalam menimbulkan penurunan berat badan.